Batman had a Weapon: socio-political influences of the construction of archetype morals in the 1930’s - Lima, Savio Queiroz (Revista Crítica Histórica, 2019)
This paper aims at historically analyzing the development of a comic book fictional character’s moral conduct development and its relationship with arms policy in the United States of America in the 1930s. In the archetypal construct of the superhero Batman, created in 1939, there is a transition element: there is an element in transition: the use of firearms by the hands of the fighting crime protagonist. This paper refines the relationships between the socio-cultural dynamics of the United States related to public security and civil liberties regarding giving firearm license to citizens through historical contextualization, the introduction of narrative excerpts from their original sources, and historiographical criticism of the investigative process. This scholarly work reflects on the editorial stance regarding the character-product that was rising in the market of the entertainment-culture industry: to avoid using firearms — moral conduct related to romanticized combating of crime. This narrative process belongs to a discourse network related to the changing imaginary that took place in the United States in face of the growth of organized crime and several news reports about crimes that have dismayed the population.